Рhysics and design of wide-aperture bipolar particle sources - Dudin, S.V. (Вопросы атомной науки и техники, 2013)
A review of known designs of bipolar particle sources is presented classifying them by spatial or temporal separation of the oppositely charged particles. Both ion-electron and ion-ion sources are considered. Possibilities of creating bipolar ion-ion source are discussed basing on recent research results from Ecole Polytechnique (France) and from V.N. Karazin Kharkоv National University (Ukraine), particularly on comparative study of the sources with magnetic and electrostatic electron filters.